HERMENEUTICAL PHENOMENOLOGY AND THE STUDY OF ART: A NOTE ON INTERDISCIPLINARITY - Cristian HAINIC (Studia Universitatis Babeș-Bolyai. Philosophia, 2015)
On the grounds that art cannot be subsumed anymore to the principles that have provided it with a certain sense of unity throughout history and that an ideal notion of art can no longer be defended, this paper investigates the hermeneutic and pragmatic roots of the recent philosophical current of “everyday aesthetics” in order to determine a baseline for the study of art. After pointing out the so-called “destructive” dimension of hermeneutical phenomenology, the paper counters the idealistic approach to art and concludes that art may and should be reintegrated within the lived life of a historically-determined community and cultural context. A key finding of the paper consists in declaring the interdisciplinary potential of the latter idea, which parallels Steve Fuller’s critique of interdisciplinarity as mere departmental flexibility and adaptability.